First Results from a Panchromatic HST/WFC3 Imaging Study of the Young, Rapidly Evolving Planetary Nebulae NGC 7027 and NGC 6302 - Joel H. Kastner (Galaxies, 2020)
We present the first results from comprehensive, near-UV-to-near-IR Hubble Space Telescope Wide Field Camera 3 (WFC3) emission-line imaging studies of two young planetary nebulae (PNe), NGC 7027 and NGC 6302. These two objects represent key sources for purposes of understanding PNe shaping processes. Both nebulae feature axisymmetric and point-symmetric (bipolar) structures and, despite hot central stars and high nebular excitation states, both harbor large masses of molecular gas and dust. The sweeping wavelength coverage of our Cycle 27 Hubble Space Telescope (HST)/WFC3 imaging surveys targeting these two rapidly evolving PNe will provide a battery of essential tests for theories describing the structural and chemical evolution of evolved star ejecta. Here, we present initial color overlays for selected images, and we highlight some of the first results gleaned from the surveys.